Changes in the Histological Appearance of White Fat in Young Rats as a Result of Different Exercise Intensities - Ronny Lesmana; Diandra Syifa; Yuni Pratiwi; Aziiz Rosdianto; Siti Mukarromah; Hanna Goenawan; Putri Tessa (WMJ (Warmadewa Medical Journal), 2023)
Sedentary lifestyle can cause the accumulation of energy reserves in the form of lipids in white adipose cells. Lifestyle modification by means of exercise is done to reduce fat reserves in white adipose tissue (WAT). This study aims to determine the effect of exercise in various intensities on the histological changes of white adipose cells. Research method exploratory with Federer formula to determine the number of samples carried out. Using 28 Wistar rats located at the Central Laboratory of Padjadjran University, Sumedang from May to June 2022. The data taken were the average diameter Â± standard error (SEM) of the inguinal white adipose cells of the experimental rats. Data analysis using Microsoft Excel 2016 and SPSS v.28 software. Of the 28 samples studied, only 25 samples met the inclusion criteria. Group K is 0.15% (p = 0.024) greater than P2, and 0.25% (p 0.001) is greater than P3. The P1 group had a value of 0.17% (p = 0.025) greater than P3. Moderate and vigorous exercise can be used to reduce the size of white adipose cells. While low-intensity exercise is considered ineffective. Further research can be carried out to assess changes in white adipose cells based on exercise intensity from other sides besides their morphology. Keywords: Histological, White Adipose Tissue, Exercise